Atomically monodisperse nickel nanoclusters as highly active electrocatalysts for water oxidation. Issue 18 (25th April 2016) - Joya, Khurram S.; Sinatra, Lutfan; AbdulHalim, Lina G.; Joshi, Chakra P.; Hedhili, M. N.; Bakr, Osman M.; Hussain, Irshad
Abstract : Atomically precise, highly monodisperse and electrochemically robust Ni nanoclusters for water oxidation catalysis exhibit remarkably low overpotential for anodic oxygen evolution reaction. Abstract : Achieving water splitting at low overpotential with high oxygen evolution efficiency and stability is important for realizing solar to chemical energy conversion devices. Herein we report the synthesis, characterization and electrochemical evaluation of highly active nickel nanoclusters (Ni NCs) for water oxidation at low overpotential. These atomically precise and monodisperse Ni NCs are characterized by using UV-visible absorption spectroscopy, single crystal X-ray diffraction and mass spectrometry. The molecular formulae of these Ni NCs are found to be Ni4 (PET)8 and Ni6 (PET)12 and are highly active electrocatalysts for oxygen evolution without any pre-conditioning. Ni4 (PET)8 are slightly better catalysts than Ni6 (PET)12 which initiate oxygen evolution at an amazingly low overpotential of ∼1.51 V ( vs . RHE; η ≈ 280 mV). The peak oxygen evolution current density ( J ) of ∼150 mA cm −2 at 2.0 V ( vs . RHE) with a Tafel slope of 38 mV dec −1 is observed using Ni4 (PET)8 . These results are comparable to the state-of-the-art RuO2 electrocatalyst, which is highly expensive and rare compared to Ni-based materials. Sustained oxygen generation for several hours with an applied current density of 20 mA cm −2 demonstrates the long-term stability and activity of these Ni NCs towards electrocatalytic water oxidation. This unique approach provides a facile method to prepare cost-effective, nanoscale and highly efficient electrocatalysts for water oxidation.